Arctic storm rising (Nick Flynn novels, 1, 1, 2021)
After a CIA covert mission goes badly awry, U.S. Air Force intelligence officer Nicholas Flynn is exiled to guard a remote radar post along Alaska's Arctic frontier. This dead-end assignment is designed to put his career permanently on ice, but Flynn's not the type to fade quietly into obscurity. As winter storms pound Alaska and northern Canada, Russian aircraft begin penetrating deep into friendly airspace. Are these rehearsals for a possible first strike, using Russia's new long-range stealth cruise missiles? Or is some other motive driving the Kremlin to take ever-increasing risks along the hostile Arctic frontier separating two of the world's great powers? When an American F-22 collides with one of the Russian interlopers, things go south fast, in seconds, missiles are fired. There are no survivors. Despite horrific weather, Flynn and his security team are ordered to parachute into the area in a desperate bid to reach the crash sites ahead of the Russians. It's now obvious that the Pentagon and CIA are withholding vital information, but Flynn and his men have no choice but to make the dangerous jump. Soon they're caught in a deadly game of hide-and-seek with Spetsnaz commandos operating covertly on American soil. It seems that the F-22s and their Russian counterparts aren't the first aircraft to have gone missing in these desolate mountains. The Kremlin is hunting for the first prototype of its new stealth bomber, which vanished on what was supposed to be a test flight, while loaded with nuclear-armed stealth cruise missiles. As Russia and the U.S. square off on the brink of all-out-war, it's up to Nick to find the missing bomber, and prevent a potential nuclear holocaust.

Countdown to midnight: a novel (Nick Flynn novel, 2,, 2022)
Nick Flynn is back in action, and he has a new employer—a shadowy intelligence outfit whose roots go back to the very beginning of the Cold War. But his first mission for them almost becomes his last. While meeting with a high-ranking Iranian dissident in the Austrian Alps, Flynn is ambushed and nearly killed… just after learning that Iran and Russia are working together on a mysterious project—one they have codenamed MIDNIGHT. Flynn is determined to uncover MIDNIGHT’s lethal secrets. Why are Moscow and Tehran covertly retrofitting a massive oil tanker in an Iranian port? What purpose lies behind their closely guarded effort, the brainchild of Pavel Voronin—a ruthless billionaire allied with Russia’s autocratic president? Flynn and his new team plan to put an end to the nefarious project, but they’re dogged at every step by Voronin’s hired Raven Syndicate killers—elite veterans of Russia’s special forces and intelligence services. As they track the enemy from the streets of Vienna to deep inside hostile Iran, Flynn and his crew must repeatedly risk their lives to pierce the layers of deception around this shadow war. It’s a race against time to stop Voronin from launching his terrifying new weapon against the United States—potentially killing hundreds of millions and overturning the world’s balance of power forever. The odds are stacked high against Flynn and his team… but that’s never stopped Nick before.

Weapons of opportunity: a novel (Nick Flynn novel, 3,, 2023)
"When Nick Flynn left the US Air Force to join the Quartet Directorate, he did so with the full knowledge that no one could ever know. This covert private force--called Four by its members--promised him the chance to lead his own missions and make his own decisions. When a former senior CIA executive goes dark, Flynn and his team are ready to step in. What begins as a quiet check on his home turns into a firefight against a familiar enemy who is more dangerous than ever"--